Aspects of formal volunteering that contribute to favourable psychological outcomes in older adults - Jongenelis, Michelle; Jackson, B.; Warburton, J.; Newton, R.U.; Pettigrew, Simone (SPRINGER, 2022)
Although there is a large body of evidence documenting the benefits of engagement in formal volunteering among older people, research assessing the specific aspects of the volunteering experience that are associated with these benefits is limited. Accordingly, the objective of this study was to (i) examine the aspects of volunteering that predict improvements or declines in older people’s psychological outcomes over time and (ii) assess the extent to which demographic characteristics and time spent engaging in informal volunteering moderate the relationship between aspects of volunteering and potential outcomes. At Time 1, non-volunteering Australian older adults completed measures assessing their subjective well-being, eudemonic well-being, and psychological resources and were asked to commence volunteering. At Time 2 (six months later), participants completed the same measures and reported on their volunteering experiences. Among the 108 older adults who provided usable data at both time points (average age = 69.86 years, 64% women), the degree to which participants felt overwhelmed by their volunteer work significantly predicted declines in subjective well-being and psychological resources. The perceived importance of the cause for which participants reported volunteering and the perceived meaningfulness of the specific activities undertaken predicted improvements in these outcomes. Volunteering roles for older adults that (i) are not considered overwhelming, (ii) fulfil their desire to volunteer for a cause about which they are genuinely concerned, and (iii) involve activities perceived to be meaningful are likely to produce the favourable psychological outcomes.